Value-driven attentional capture in neglect. (December 2018) - Bourgeois, Alexia; Saj, Arnaud; Vuilleumier, Patrik
Abstract: Objective: Recent studies suggest that motivational cues such as rewards may be a powerful determinant of attentional selection, both in healthy subjects and in brain-damaged patients suffering from neglect. However, the exact brain mechanisms underlying these effects and their relation to other well-known attentional systems are still poorly known. Methods: We designed a visual search paradigm to examine how value-based attentional priority could modulate spatial orienting in patients with pathological biases due to neglect after right hemispheric stroke. Targets were preceded by exogenous valid or invalid spatial cues, in the presence or absence of distractors that were associated with high reward values subsequent to an initial reinforcement training phase. Results: We found that the learned reward value of distractors interfered with spatial reorienting toward the left (neglected) side when neglect patients were invalidly cued to the right side. Moreover, the presence of reward-associated distractors in the contralesional field interfered most with the detection of task-relevant targets on the same side, and this interference was exaggerated with more severe neglect. Voxelwise anatomical lesion analysis indicated that damage to the right angular gyrus, as well as lateral occipital and inferior temporal areas of the right hemisphere, were associated with stronger value-driven attentional effects. Conclusions: Visual stimuli previously associated with rewards receive higher attentional priority during visual search despite pathological spatial biases due to neglect, and thus interfere with orienting to contralesional targets, presumably by competing with top-down mechanisms controlling exogenous spatial attention. Reward signals may bias neural activity evoked by visual stimuli, independent of conscious control, through a common priority map integrating several different attentional influences. These results do not only provide novel insights to link spatial orienting and motivational signals within current models of attention, but also open new perspectives that may usefully be exploited for neurological rehabilitation strategies in patients suffering from attentional deficits and neglect.